Program Kebersihan Lingkungan Pondok untuk Memberikan Kenyamanan Santri di Pondok Pesantren Al-Falah Siwalanpanji Buduran Sidoarjo - Akbar Adiyoso (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study is motivated by the importance of maintaining cleanliness in the boarding school environment to create comfort for students, as well as the existing issues related to suboptimal cleanliness management at Al-Falah Islamic Boarding School Siwalanpanji, Buduran, Sidoarjo. The purpose of this study is to analyze the environmental cleanliness program in improving students’ comfort. The method used in this activity is a participatory community service approach, which involves all elements of the boarding school, especially the students, directly in the implementation of the cleanliness program. The results show that the cleanliness program is carried out through three main stages: planning, which includes problem identification, program formulation, and preparation; implementation in the form of cleaning activities such as maintaining the boarding school environment, organizing facilities, and maintaining infrastructure; and evaluation, which indicates an improvement in cleanliness and students’ comfort, although there are still challenges in maintaining consistency. Therefore, it can be concluded that the environmental cleanliness program plays an important role in creating a clean, healthy, and comfortable environment, as well as in fostering students’ discipline and sense of responsibility in a sustainable manner.